PENGUKURAN PRODUKTIVITAS PADA LINI PRODUKSI DI PTPN IX (PERSERO) KOPI BANARAN MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) - , RIANTINO ANGGA ZANUAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
By increasing productivity, will enhance the quality and well-being company. Business competition between companies, which encourages companies increase productivity for the company's development in the future. To determine the level of productivity in PTPN IX (Persero) Coffee Banaran necessary to measure productivity in the production line. In addition, knowing the factors that affect the productivity improvement. Obtained from the level of productivity, the productivity of the planning done for the development of the company in the future. Productivity measurement using objective methods matrix (OMAX). Productivity measurement is done by observing the real conditions in PTPN IX Persero) Coffee Banaran that exist on the production line. OMAX concept is to develop a working group to the performance criteria in a matrix. Stages of productivity measurement with OMAX method contained in the analysis and evaluation of existing in this final. There are three criteria: efficiency, effectiveness, and inferential measurement is divided into 6 ratio. Results of performance indicators is now the largest in July that is 429.76, while the smallest current performance indicators in October is 176.36. OMAX in a matrix can be separated into good grades, standards, and bad values of the scales. The ratio of the weight but have a bad in the category by the number of periods (months) most, needs extra attention, because this ratio has an important role for the company.